Amputation for chronic pain and/or functional impairment of a limb - Evelyne Linden; Koen Peers; Carlotte Kiekens (Medical Journals Sweden, 2021)
Objective: To evaluate the impact of a lower limb amputation for chronic pain and/or functional impairment on pain and participation in daily living activities and to assess the use of prostheses. To improve decision-making for this controversial treatment. Design: Survey. Setting: University hospital. Subjects: Patients who had an amputation of a lower limb for chronic pain and/or functional impairment. Results: Eighty-one percent of the patients were satisfied with the amputation and would decide to undergo an amputation again under the same conditions. Sixty-nine percent of the patients reported an improvement in pain, 69% an improvement in mobility, 75% in daily living activities, and 56% an improvement in sleep. Seventy-five percent of the patients used their prosthesis on a daily basis. Conclusion: Most patients who underwent an amputation in our hospitals for chronic pain and/or functional impairment of a lower limb were satisfied and reported an improvement in function and pain. Lay abstract Therapeutic decision-making for chronic pain and/or functional loss in a lower limb is a complex problem. Many articles have been devoted to chronic pain, and current guidelines mention a lot of treatment options. However, patients can still experience a lot of pain and/or functional loss after having tried many treatments. Some of these patients request an amputation. Most physicians refrain from this treatment, since it is very drastic, irreversible, and there is a lack of evidence regarding the outcome. To our knowledge only a few case reports and a select number of case series have been published to date about amputation for chronic pain and/or functional loss in a lower limb, and these show variable results. This study followed a small group of patients in University Hospitals Leuven, Belgium, who underwent a lower limb amputation for this complex problem. Most of these patients were satisfied with their amputation. They reported an improvement in function and pain, and would decide to undergo an amputation again under the same conditions.